Behaviour of durum wheat cultivars towards deoxynivalenol content: A multi-year assay in Italy - Amoriello, Tiziana; Belocchi, Andreina; Quaranta, Fabrizio; Ripa, Cecilia; Melini, Francesca; Aureli, Gabriella (Italian Journal of Agronomy, 2017)
The deoxynivalenol (DON) occurrence in durum wheat (Triticum durum Desf.) kernels is a key food safety issue, hence more and more attempts have been made to increase the availability of resistant cultivars. Within this framework, this work focused on the analysis of the behaviour of several durum wheat cultivars widely grown in Italy in relation to the level of deoxynivalenol contamination in whole milled kernels. A total of 2844 samples were submitted for deoxynivalenol analysis by enzyme-linked immuno-sorbent assay. The statistical analysis by generalised linear models provided a trend ranking of durum wheat cultivars on the basis of the deoxynivalenol contamination level, depending on each cultivation area assayed. This study provided a better understanding of cultivar susceptibility to mycotoxin accumulation in grains. The role of the factor cultivar has clearly emerged. However, other environmental factors, such as growing area, have a great influence on the DON concentration levels in the cultivars tested.